Faʻāliyah Istikhdām Istirātījiyyah al-ʻIqāb ʻalá Mahārah al-Kalām ladā Ṭullāb Maʻhad Tāpūz Bāriyāmān Sūmaṭrah al-Gharbiyyah - Aditya Denika; Anas, Albaihaqi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Teaching Arabic is a process that aims to develop students' abilities and guide them towards mastering the language by using it in their daily lives. The implementation of the punishment strategy at the Tapuz Pariaman Institute is one of the activities that contribute to improving students' Arabic language skills, as students are required to use Arabic throughout the day. This study aimed to find out the effectiveness of using the punishment strategy in improving the speech skills of students of the Tapuz Pariaman Institute in West Sumatra. This research is qualitative research using the descriptive analysis method. Data were collected by interview and observation method. After processing and analyzing the data, the researcher obtained the results of the research that the application of the punishment strategy at the Tapuz Pariaman Institute is effective in upgrading the Arabic language speech skill of students. Use sanctions as an educational tool not only to promote discipline, but to achieve educational goals through useful educational activities, such as memorizing Arabic vocabulary and conducting dialogues. Punishment has also proven effective in motivating students to abide by the rules and develop their language skills continuously. يعدّ تعليم اللغة العربية عملية تهدف إلى تنمية قدرات الطلاب وتوجيههم نحو إتقان اللغة من خلال استخدامها في حياتهم اليومية. يعدّ تطبيق إستراتيجية العقاب في معهد تافوز باريامان أحد الأنشطة التي تسهم في تحسين مهارات الطلاب في اللغة العربية، حيث يُلزم الطلاب باستخدام اللغة العربية طوال اليوم.. هدفت هذه الدراسة إلى معرفة فعالية استخدام إستراتيجية العقاب في تحسين مهارة الكلام لدى طلاب معهد تافوز باريامان في سومطرة الغربية. هذا البحث بحث كيفي باستخدام أسلوب التحليل الوصفي. تم جمع البيانات عن طريقة المقابلة واللاحظة. بعد معالجة البيانات وتحليلها، حصل الباحث على نتائج البحث أن تطبيق إستراتيجية العقاب في معهد تافوز باريامان فعال في ترقية مهارة الكلام باللغة العربية لدى الطلاب. استخدام العقوبات كأداة تربوية ليست فقط لتعزيز الانضباط، بل لتحقيق أهداف تعليمية من خلال أنشطة تعليمية مفيدة، مثل حفظ المفردات العربية وإجراء الحوارات. كما أن العقاب قد أثبت فعاليته في تحفيز الطلاب على الالتزام بالقواعد وتطوير مهاراتهم اللغوية بشكل مستمر.